Một trăm 100 essay plans for economics - Ernie Jowsey (Oxford University Press, 1998)
The essay plans contained in the book cover the most commonly asked questions on each syllabus area of microeconomics and macroeconomics. The author has used a wealth of experience in teaching and examining in economics to provide a useful manual for all students of the subject. Ernie Jowsey provides clear, practical help both in preparing material and in writing up the final essay. The book has a section providing advice on how to write essays in the subject of economics, and each essay plan is organised according to the same structure for clarity (Introduction; Main Arguments; Conclusion; Further Reading). Most are illustrated with a simple figure. The book functions as a summary of important topics and provides the student with a proactive method of learning and revision. Working through 100 Essay Plans in Economics can therefore be used as alternative way of covering the introductory syllabus alongside the economics principles texts. This makes the book an invaluable learning aid to students embarking on first year undergraduate economics courses, as well as to those preparing for essay paper examinations in economics